Digital competencies of educators. Before and after the pandemic: experience report from Chita Pedagogical College - Sidorenko, Oksana [Verfasser] (My University, 2022)
"The Chita Pedagogical College has focused early on the development of digital competences. At the core of all innovation are the digital didactics of Vocational Education. An educational communication net work was established in order to create an environment which encourages teachers to enhance their digital competences. The transition to remote learning due to the COVID-19 pandemic went smoothly at the Chita Pedagogical College." (Author's abstract ; BIBB-Cloud)
Keywords: I 2.3.4 Asien; P 3.2.3 Lehrer; 370; Berufsbildung; Pandemie; Russland; Digitalkompetenz; Medienkompetenz; Lehrer